Identifikasi Problem Penilaian Psikomotorik Dalam Pembelajaran PAI di SMPN 1 Jenangan - Sofi Sifaul 'Aini; Sofia Wahyu Amala; Sofwatun Nisa; Syifaul Kholilain; Syifaun Nurun Nikmah; Wahyu Restu Sukmawati (Muaddib: Jurnal Pendidikan Agama Islam, 2024)
The ability of students to develop fundamental mental, physical and social skills is known as psychomotor assessment, and it serves as a catalyst for the development of higher talents in a person. This psychomotor evaluation is very important in learning Islamic Religious Education (PAI) because it can measure students' abilities in the subject. The purpose of this study is to determine the challenges faced by PAI teachers in implementing psychomotor assessment at SMPN 1 Jenangan. Descriptive qualitative method was used in this study, and data were collected using school environment analysis sheet, interview protocol, and observation. According to this study, there are some major obstacles in implementing psychomotor assessment on students, such as lack of training for teachers, challenges in creating assessment tools, lack of learning time, and inadequate facilities. This study suggests that to facilitate more optimal development of psychomotor assessment, teachers should receive training on psychomotor assessment techniques and skills.